2015
DOI: 10.1007/s10815-015-0474-6
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis in patients with total sperm immotility

Abstract: Our work suggests that WES is an effective strategy, especially as compared with conventional sequencing, to study highly heterogenic genetic diseases, such as sperm immotility. For future work we expect to expand the analysis of WES to the other four patients and complement findings with expression analysis or functional studies to determine the impact of the novel variants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 56 publications
1
31
0
Order By: Relevance
“…However, there are no consensus if DFS is a genetic disorder. Indeed, no association between DFS and defects in genes that code for AKAP3 and AKAP4 proteins were found 110111112…”
Section: Main Factors Affecting Sperm Motilitymentioning
confidence: 99%
“…However, there are no consensus if DFS is a genetic disorder. Indeed, no association between DFS and defects in genes that code for AKAP3 and AKAP4 proteins were found 110111112…”
Section: Main Factors Affecting Sperm Motilitymentioning
confidence: 99%
“…The Akap4defficient mice resemble the asthenozoospermic phenotype (Fang et al 2019) observed in men. However, apart from these two case reports, AKAP4 mutations were not found in other cohorts of DFS patients, indicating currently limited evidence for this gene defect (Turner et al 2001a, b;Yang et al 2015b;Pereira et al 2015).…”
Section: Akap4mentioning
confidence: 83%
“…In the report of Moretti et al ., a weak labelling for AKAP4 was demonstrated in the group of patients with severely reduced sperm motility and disorganised FS; however, none of these cases was characterised by the typical for DFS ultrastructural features of the sperm flagellum (Moretti et al ., ). The subsequent report did not add further evidence towards the hypothesis that Akap 3/4 are the genetic causes of the DFS phenotype (Pereira et al ., ). Thus, the role of AKAP3/4 genetic mutation in the development of DFS was described only in one DFS case (Baccetti et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…demonstrated a partial deletion in AKAP4 and AKAP3 genes and the absence of the protein AKAP4 in one of five patients with DFS (Baccetti et al ., ). At the same time, other researches revealed no differences in the content of the proteins AKAP4 or AKAP3 in DFS spermatozoa compared to normal spermatozoa (Turner et al ., ; Moretti et al ., ; Pereira et al ., ). Recently, four homozygous mutations in the DNAH1 gene encoding for axonemal inner arm dynein heavy chains were identified in seven patients with MMAF (Ben Khelifa et al ., ).…”
Section: Introductionmentioning
confidence: 97%